Kierkegaard and his contemporaries : the culture of golden age Denmark - Stewart, Jon, 1967- (Kierkegaard studies. Monograph series, 2003)
Annotation Interpreting Kierkegaard in the general context of Golden Age Denmark, this interdisciplinary anthology features articles which treat his various relations to his most famous Danish contemporaries. It aims to see them not as minor figures laboring in Kierkegaard's shadow but rather as significant thinkers and artists in their own right. The articles illuminate both Kierkegaard's influence on his contemporaries and their varied influences on him. By means of the analyses of these various relations, aspects of Kierkegaard's authorship are brought into new and insightful perspectives. The featured essays treat some of the most important figures from the time, representing the fields of philosophy, theology, literature, criticism and art.